A cross-cultural basis for public service? Public service motivation measurement invariance in an original survey of 23, 000 public servants in ten countries and four world regions. Issue 6 (2nd November 2021) - Mikkelsen, Kim Sass; Schuster, Christian; Meyer-Sahling, Jan-Hinrik
Abstract: Public service motivation (PSM) is a core concept in public administration, studied in surveys across numerous countries. Whether these studies accumulate comparable knowledge about PSM crucially depends on PSM measurement invariance: that PSM has a similar measurement structure in different national contexts. Yet, large-scale cross-country research to address this conundrum remains scant. Drawing on an original survey of 23, 000 public servants in ten countries in Eastern Europe, Asia, Latin America, and Africa, our paper addresses this gap. Replicating Kim et al.'s 16-item scale, we find partial metric invariance for the four PSM dimensions in eight countries, but scalar non-invariance. This suggests that results from structural equations about the causes and consequences of PSM may be compared across most countries, yet means of PSM and its dimensions are not generally comparable. PSM research thus cannot adjudicate in which countries public service motivation is higher or lower on average but can compare relationships between PSM and individual characteristics or management practices between countries. Our findings underscore the cross-cultural basis of public service motivation and its limits.